Optimizing Digital Management of Research and Collaboration With Academic Information Manager - Peyman Nejat, MD; Vitali Fedosov, MD, PhD; Chady Meroueh, MD; Hugo Botha, MB, ChB; Svetlana Herasevich, MD, MS; Ing Tiong, MS, MA; David Martin, MD, PhD; Brian W. Pickering, MD, MS; Vitaly Herasevich, MD, PhD (Mayo Clinic Proceedings: Digital Health)
Objective: To evaluate the efficacy, efficiency, and usability of the current iteration of the fully automatic Academic Information Manager (AIM) within the Department of Anesthesiology and Perioperative Medicine. Participants and Methods: AIM was designed, developed, and deployed to address the growing need for digital information management in academic research. In a randomized, unblinded crossover study from April 1, 2020 to August 1, 2020, 15 participants completed 8 tasks using both AIM and conventional information retrieval methods. We assessed task completion time (efficiency), task completion status and accuracy (efficacy), subjective mental workload using the National Aeronautics and Space Administration Task Load Index (NASA-TLX), and system usability using System Usability Scale questionnaire, with and without AIM. Results: Using AIM resulted in a significant time saving, with significantly higher task completion (99% vs 57%) and accuracy (99% vs 59%) compared with conventional methods. The NASA-TLX scores with AIM showed a statistically significant decrease in mental demand, temporal demand, effort, and frustration, along with an increase in performance, compared with those without AIM. The System Usability Scale score for AIM was above the 90th percentile. Conclusion: Using AIM, we observed a significant increase in efficacy and efficiency, along with a decreased mental workload, as measured by NASA-TLX, and improved usability scores. Implementing AIM will help new investigators quickly and intuitively identify ongoing research at our institution. It will also enable them to broadcast their research interests to find potential collaborators.